Selling Participation to Audiences in China - Kuo Huang; Naren Chitty (Global Media Journal: Canadian Edition, 2009)
Media globalization is facilitated by the development of new technologies within a framework of digitization and convergence. Contemporary new media provide networks through which the mingling of media occurs, shaping a “multi-mediacy” age, and a connecting of mediated/mediating venues in a condition of “immediacy”. Additionally, the business of communication has evolved from being the “communication of business” to the “business of business”. Multi-mediacy and immediacy have generated new avenues of profit from media. The paper will draw on Chitty’s theorization on web transactional venues to discuss new ways of farming of revenue from media. Media revenues have in the past and today been drawn from licence fees, media subscriptions and advertising. Today, media networks also sell “participation” to audiences directly by charging for text message voting/gaming, or sell a range of products and services through web-venue based commerce. This paper will undertake case studies to examine the increasing trend of “direct audience payment for participation”. The case studies that will be used are (A) the intervention of Chinese Service Providers in reality TV shows and (B) E-commerce on the Internet. Monternet (mo[bile I]nternet) and Linktone are investigated as Service Providers (SPs) and the consumer-to-consumer (C2C) website www.taobao.com is studied compared with Eachnet (eBay in China). The paper will also investigate the influences of “direct audience payment for participation” on the quality of media products and communication flow between media and audience and generally discuss the consequences of the “direct audience payment for participation” from the perspective of communication ethics.